OVERALL LABOR EFFECTIVENESS (OLE) ANALYSIS FOR PRODUCTIVITY IMPROVEMENT IN THE ASSEMBLY PROCESS OF THE MUSICAL INSTRUMENT MANUFACTURING INDUSTRY - Rheidika Aryaduta; Ali Parkhan (Jurnal Disprotek, 2026)
Manual-based piano assembly industries rely heavily on workforce effectiveness; however, productivity performance often fails to meet company targets. In the Disklavier Assembly Grand Piano section, labor productivity did not achieve the expected 15% increase, from 0.193 to 0.222 units/person/hour, indicating the need for a systematic evaluation of workforce performance to identify underlying problems. This study aims to evaluate labor effectiveness using the Overall Labor Effectiveness (OLE) approach, which consists of three key dimensions: Availability, Performance, and Quality. The research employed direct observation and daily operational data collection from March to May 2025, resulting in 59 observation data points. The analysis involved calculating OLE values and identifying the main causes of performance gaps as the basis for improvement proposals. The results show an average OLE of 58%, which is below the international benchmark of 85%. The Availability Ratio reached 91%, while the Performance Ratio was only 65% and the Quality Ratio was 92%. Low performance was mainly caused by time waste, limited work aids, workload imbalance, and the absence of visual control systems, whereas quality issues were primarily driven by manual assembly errors and insufficient precision tools. The implementation of improvement proposals, including visual control systems, additional work aids, and process standardization, increased productivity by 12.3%, from 0.193 to 0.217 units/person/hour. These findings confirm that the OLE approach is effective for improving productivity in manual labor-based piano assembly operations. ANALISIS OVERALL LABOR EFFECTIVENESS (OLE) UNTUK PENINGKATAN PRODUKTIVITAS PADA PROSES PERAKITAN PADA INDUSTRI MUSIKIndustri perakitan piano yang masih didominasi proses manual sangat bergantung pada efektivitas tenaga kerja, namun pada praktiknya sering menghadapi permasalahan produktivitas yang belum mencapai target perusahaan. Pada section Disklavier Assembly Grand Piano, produktivitas kelompok kerja belum mampu memenuhi target peningkatan sebesar 15%, yaitu dari 0,193 unit/orang/jam menjadi 0,222 unit/orang/jam. Kondisi ini menunjukkan perlunya evaluasi sistematis terhadap kinerja tenaga kerja untuk mengidentifikasi faktor penyebab rendahnya produktivitas. Penelitian ini bertujuan untuk mengevaluasi efektivitas tenaga kerja menggunakan pendekatan Overall Labor Effectiveness (OLE), yang mencakup tiga dimensi utama: Availability, Performance, dan Quality. Metode penelitian dilakukan melalui observasi langsung dan pengumpulan data operasional harian selama periode Maret–Mei 2025 dengan total 59 data pengamatan. Analisis dilakukan dengan menghitung nilai OLE serta mengidentifikasi penyebab utama rendahnya kinerja sebagai dasar penyusunan usulan perbaikan. Hasil pengukuran menunjukkan nilai rata-rata OLE sebesar 58%, masih di bawah standar internasional sebesar 85%. Availability Ratio mencapai 91%, namun Performance Ratio hanya 65% dan Quality Ratio sebesar 92%. Rendahnya performance disebabkan oleh pemborosan waktu kerja, keterbatasan alat bantu, ketidakseimbangan beban kerja, serta ketiadaan sistem visual, sedangkan permasalahan kualitas dipicu oleh kesalahan perakitan manual dan kurangnya alat bantu presisi. Implementasi usulan perbaikan berbasis visual control, penambahan alat bantu, serta standarisasi proses terbukti meningkatkan produktivitas sebesar 12,3%, dari 0,193 menjadi 0,217 unit/orang/jam. Hasil ini menunjukkan bahwa analisis OLE efektif dalam meningkatkan produktivitas pada industri perakitan piano berbasis kerja manual.